Investigation of dissolution resistance of blank and gas-nitrided carbon steels in stationary SAC305 solder alloy melt - Benke M.; Salyi Zs.; Kaptay G. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The objective of the present study is to investigate the suitability of a series of gas-nitrided steels with varying C content as candidates for wettable selective soldering tool materials with enhanced lifetime. ɛ and γ’ iron-nitrides were formed by gas nitriding on quenched and tempered DC04, C45, CK60 and S103 type steels. Contact angle measurements revealed that all four nitrided steels exhibit good wetting with SAC305 solder melt. In order to investigate the dissolution reactions between the nitrided steels and the solder alloy, an equipment was assembled in which the samples were submerged into stationary SAC305 solder melt for different time durations. Evidences of dissolution reactions and other degradation processes were searched for using scanning electron microscopy and energy dispersive X-ray spectroscopy. It was observed that no Fe dissolution occurred between the samples and stationary SAC305 solder melt during continuous tests with durations up to 20 days. Furthermore, no other visible degradation reactions occurred between the samples and melt during the experiments. It was concluded that gas-nitrided steels show good wetting with Sn-based solder melts which is combined with excellent resistance against Fe dissolution in a high Sn-containing molten solder. Thus, gas-nitrided steels/iron can be potential materials for wettable selective soldering tools with improved lifetime.